Relevance of Six Directions Worship Philosophy in Sigalovada Sutta to Indonesian Character Education - Jarmini Jarmini; Suroso Suroso; Eka Putu Agy Wijayanto (STABN RADEN WIJAYA WONOGIRI, 2024)
This article discusses the relevance of the philosophy of worshiping the six directions found in the Sigalovada Sutta to character education in Indonesia, focusing on the Buddhist perspective. The aim of this research is to explain how the concept of worshiping the six directions in the Sigalovada Sutta elucidates its relevance in shaping strong and responsible character. The research methodology employed is a literature review of relevant Buddhist texts, including the Sigalovada Sutta. The findings indicate that the philosophy of worshiping the six directions practiced by Sigala is not interpreted as worshiping the directions themselves, but as symbols of respect for parents (east), teachers (south), children or spouses (west), friends and siblings (north), workers/servants (below), and holy persons such as ascetics and spiritual teachers (above). The philosophy of worshiping the six directions in the Sigalovada Sutta is relevant to character education in Indonesia as it pertains to the values of character, namely: 1) religious, 2) honesty, 3) tolerance, 4) discipline, 5) hard work, 6) democratic, 7) appreciation of achievement, 8) patriotism, 9) communicative, 10) love of peace, 11) social concern, and 12) responsibility. Based on these research findings, this article seeks to contribute to the discourse on how religious philosophy can be practically applied in the context of modern education.